Balinese Traditional Games to Develop Children's Resilience in Early Childhood Education - Tria Ariani, Nyoman Wiraadi (International Journal of Instructions and Language Studies, 2024)
The Covid-19 pandemic has had a profound impact on children, with restrictions and changes in daily routines affecting their psychological well-being, including their resilience. This study examines the role of traditional Balinese games, specifically Curik-curik, in fostering children's resilience. Using the case study method, we analyze the aspects that shape children's resilience during the game of Curik-curik. The results reveal that this traditional game provides a natural and effective means for children to communicate their feelings, reducing their worries and anxieties. Moreover, participating in Curik-curik enables children to develop self-control, emotional management, and problem-solving skills, preparing them to face real-life changes and obstacles. By engaging in traditional Balinese games, children can cultivate resilience and be better equipped to tackle new challenges in their growth journey.